Therapeutic Hypothermia by Cold Intravenous Fluid and Short Outcome in Asphyxiated Newborn - Ashraf Mohamadzadeh; Ahmadshah Farhat; Ezzat Khodashenas; Mojtaba Adineh; Aradokht Vaezi; pouya Taji; Mahdi Salimifar (Iranian Journal of Neonatology)
Background: Therapeutic hypothermia has reduced mortality and morbidity in asphyxiated newborns. The study aims to induce hypothermia by cold intravenous 10% dextrose and its effect on hospital stay and mortality in asphyxiated newborns.. Methods: Filthy one neonate with asphyxia was randomly assigned to either cold intravenous dextrose 10% for 72 hours started within 6 hours of birth with rectal temperature maintained33-34̊C (no 25 cases) or conventional care (no 26 controls). The primary outcome was hospital stay and death. The optimal rate of rewarming did not exceed the rate of 0.5 ̊C/h. All of them had birth weight ≥ 2500 grams and gestational age ≥ 36 weeks. Those with congenital anomalies, sepsis, DIC, and shock were excluded. Results: The two groups were the same regarding demographic and obstetric complications. Hospital stays and mortality rates were significantly lower in the case group p-values 0.05 and 0.01, respectively. Conclusion: Therapeutic hypothermia by cold intravenous dextrose is possible and can reduce hospital stays and mortality with low incomes for asphyxiated newborns.